TIR-Domain-Containing Adapter-Inducing Interferon-β (TRIF) Is Essential for MPTP-Induced Dopaminergic Neuroprotection via Microglial Cell M1/M2 Modulation - Shan, Minghui; Lin, Sen; Li, Shurong; Du, Yuchen; Zhao, Haixia; Hong, Huarong; Yang, Ming; Yang, Xi; Wu, Yongmei; Ren, Liyi; Peng, Jiali; Sun, Jing; et al. (Frontiers in Cellular Neuroscience, 2017)
Dynamic changes of two phenotypes of microglia, M1 and M2, are critically associated with the neurodegeneration of Parkinson’s disease. However, the regulation of the M1/M2 paradigm is still unclear. In the MPTP induced neurodegeneration model, we examined the concentration of dopamine (DA) related metabolites and the survival of tyrosine hydroxylase (TH) positive cells in WT and Trif-/- mice. In in vitro experiments, MN9D cells were co-cultured with BV2 cells to mimic the animal experiments. Inhibition of TRIF aggravated TH+ cell loss, and DA-related metabolites decreased. TRIF inhibition was able to interrupt the microglial M1/M2 dynamic transformation. More BV2 cells were activated and migrated across the membrane of transwell plates by siTRIF treatment. Also, TRIF interruption inhibits the transformation of BV2 cells from the M1 to M2 phenotype which played a beneficial role in neuronal degenerative processes, and increased MN9D apoptosis. Moreover, MPP+ treatment decreases the (DAT) dopamine transporter and TH synthesis by MN9D. Taken together, the current results suggest that TRIF plays a key switch function in contributing to the microglial M1/M2 phenotype dynamic transformation. The interruption of TRIF may decrease the survival of MN9D cells as well as DAT and TH protein production. The current study sheds some light on the PD mechanism research by innate inflammation regulation.